Food toxicants analysis : (Elsevier, 2007)
The book covers different aspects from the field of analytical food toxicology including emerging analytical techniques and applications to detect food allergens, genetically modified organisms, and novel ingredients (including those of functional foods). Focus will be on natural toxins in food plants and animals, cancer modulating substances, microbial toxins in foods (algal, fungal, and bacterial) and all groups of contaminants (i.e., pesticides), persistent organic pollutants, metals, packaging materials, hormones and animal drug residues